Ответы 2

  • 3,84 - (х + 0,89) = 2,3

    х + 0,89 = 3,84 - 2,3

    х + 0,89 = 1,54

    х = 1,54 - 0,89

    х = 0,65

    (х + 3,5) - 4,8 = 24

    х + 3,5 = 24 + 4,8

    х + 3,5 = 28,8

    х = 28,8 - 3,5

    х = 25,3

  • 3.84 - (x + 0.89) = 2.3 \\ 3.84 - x - 0.89 = 2.3 \\ 2.95 - x = 2.3 \\  - x = 2.3 - 2.95 \\  - x =  - 0.65 \\ x = 0.65 \\  \\  -  -  -  -  -  -  -  -  -  -  \\  \\ (x + 3.5) - 4.8 = 24 \\ x + 3.5 - 4.8 = 24 \\ x - 1.3 = 24 \\x = 24 + 1.3 \\ x = 25.3
    • Автор:

      sean953
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years